Cultural Transform di Situs Benteng Putri Hijau - Stanov Purnawibowo (Berkala Arkeologi Sangkhakala, 2011)
AbstractArchaeology not only describing about the past, but also present. The form of cultural transformation process which describe the process of archaeological record disposition in the post-depositoanal factors, one of example form describe from present. Cultural transformation of archaeological record was found in Benteng Putri Hijau site. Precipitation position of archaeological data and stratigraphy can give information about cultural transformation data and contexts remain found in archaeological deposition.